Malaysia's compliance with international treaties on women human rights / Nurul Shuhada Suhaimi, Nur Aishah Mustafah and Farah Helmy - Suhaimi, Nurul Shuhada; Mustafah, Nur Aishah; Helmy, Farah (2008)
Women human rights are human rights. These rights are recognized at the international level. There are international conventions that specify these rights. Examples of international treaties are Convention on the Elimination of Discrimination against Women (CEDAW) and Convention on the Political Rights of Women. After these treaties come into force, it is now the obligation of the state parties to incorporate them into their local legislations. Malaysia, for example, is a state pasty to CEDAW. However, not all the provisions will be domesticated into our local legislations. The reservation is due to some local factors. Implementation is a question of practicality and technicality. There are Malaysian legislations included in this research as to compare whether they really comply with the intention of the treaties that we had signed. Recommendations are given to fill in the holes in implementing international treaties regarding women human rights in Malaysia and to create awareness of the public with regards to the issue.